Design and validation of questionnaires to measure educational needs about medications in students, parents, and teachers in an elementary school - Ana M. Téllez-López; Brenda Y. Márquez Castro; Isis Beatriz Bermudez-Camps; Ivette Reyes Hernández; Maricela López Orozco; Leobardo Manuel Gómez-Oliván (GarVal Editorial Ltda., 2022)
Context: To achieve a health literacy program aimed at improving the use of medicines, it is necessary to have tools that identify educational needs through valid and reliable instruments. Aims: To validate instruments designed to evaluate the correct use of medicines in an elementary school in the state of Hidalgo, Mexico, applying the Delphi method. Methods: A descriptive, mixed study was carried out. Three questionnaires were designed based on a documentary analysis and the identification of influential variables expressed in dimensions and items, such as sociodemographic, pharmacotherapeutic, and clinical characteristics. The content validity was determined by applying the Delphi method, the mathematical model of Torgerson (MMT), and Aiken's v coefficient, while the internal reliability was determined by Cronbach's alpha value and the interobserver concordance by the Kappa index. Results: Three questionnaires were designed with 33, 48, and 44 items addressed to students, parents, and teachers respectively. The content was valid meeting the MMT criteria and Aiken's v values above 0.9. Reliability was moderate with Cronbach's alpha values of 0.6 and inter-observer agreement was moderate with Kappa index values of 0.4. Reliability and concordance values are accepted when considering the literature review and rigorous expert input. Conclusions: The designed questionnaires contain valid and reliable items that will allow obtaining the necessary information to build an education program of medication use in an elementary school considering the integration of students, parents, and teachers.